From The Higher Education Council Documentation Center Towards the National Thesis and Dissertation Center - Erol Yılmaz (Türk Kütüphaneciliği)
Dissertations and graduate theses are important information sources for researchers, particularly for faculty members. In the present article, studies on the bibliographical control of dissertations and graduate theses of Turkey is reviewed briefly. In the next stage, the topic is reviewed with respect to Higher Education Councils (HEC) Documentation Center which owns the widest collection of dissertations and graduate theses in the country. The mentioned center should be transformed to National Theses and Dissertation Center (NTDC). Finally, the problems that prevent the center to offer more productive services regarding dissertations and theses are discussed and related solutions are presented.